PHOTOMETRIC INVESTIGATION OF XX CYG - Udovichenko, S. N. (Одеські астрономічні публікації, 2017)
The photometric observations of SX Phe type star XX Cyg (V=12m, A5) were made in five nights using 48 cm reflector at the Astronomical Observatory of Odessa National University. The CCD photometer and the V filter of the UBV system was used. The variable and comparison stars monitored in the frame simultaneously. Light curves indicates a total light range 0.8 mag. A frequency analyses allow to find only one frequency of pulsating and it cause to consider this star as unique among this type. The light variation of XX Cyg can be well fitted with a single pulsation frequency during 60 years. This pulsating is in generally stable, but, there is a slight variation of period and, possibly, the light curves show, besides the primary maximum, a small bump of an amplitude of approximately 0.1 mag.